2013
DOI: 10.1016/j.ijepes.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Regional integration of renewable energy systems in Ireland – The role of hybrid energy systems for small communities

Abstract: Due to a lack of indigenous fossil energy resources, Ireland's energy supply constantly teeters on the brink of political, geopolitical, and geographical unease. The potential risk to the security of the energy supply combined with the contribution of anthropogenic greenhouse gas emissions to climate change gives a clear indication of Ireland's need to reduce dependency on imported fossil fuels as primary energy source. A feasibility analysis to investigate the available renewable energy options was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Alternative technologies offer a less costly option than incineration, with a lower environmental impact and a reduction in the volume of residual waste which requires landfilling (Goodbody and Walsh, 2013).…”
Section: Alternative Treatment Technologiesmentioning
confidence: 99%
“…Alternative technologies offer a less costly option than incineration, with a lower environmental impact and a reduction in the volume of residual waste which requires landfilling (Goodbody and Walsh, 2013).…”
Section: Alternative Treatment Technologiesmentioning
confidence: 99%
“…This study suggested PV-wind-battery hybrid as a better option. In a similar analysis, Goodbody et al 23 performed the study on integration of renewable energy systems in Ireland. System optimization was carried using HOMER, diurnal and seasonal variation of load was taken into consideration for optimization.…”
Section: Literature Surveymentioning
confidence: 99%
“…These include economic analyses of the immediate deployment of the smart grid [18], consumer awareness of smart grid [19], smart meters [20], microgeneration [21], the role of smart grids in renewable power integration [22] and high wind power integration in the electricity grid [23]. These studies variously emphasise a cost-benefit analysis of smart grid policy [24], diffusion of innovation models based on Rogers [19,20,25], the optimal (financial and environmental) regional distribution of hybrid energy systems [21], optimal (technical and economic) integration of grid-connected microgeneration technologies at household level [26] and the technical and market challenges for high wind power integration in the grid [22,23]. Where societal engagement is considered, it is largely confined to consumer acceptance/awareness and education [19,24].…”
Section: The Importance Of Contextmentioning
confidence: 99%